Retinal Screening in High-Performance Athletes: A Retrospective Analysis of Asymptomatic Peripheral Lesions in Collision and Non-Collision Sports - Nicolas Arej; Hervé Treguer; Chloé Le Cossec; Benjamin Kakona; Nicolas Mandrillon; Vivien Vasseur; Sébastien Le Garrec; Sylvain Blanchard; Sébastien Bruneau; Sophie Bonnin (Sports Medicine - Open)
Abstract Background Ocular trauma is a frequent concern among athletes, particularly those involved in collision sports. While overt injuries are well-documented, the prevalence of asymptomatic peripheral retinal lesions resulting from repetitive head or ocular trauma remains underexplored. This study aimed to assess the prevalence of these retinal lesions in elite athletes and to evaluate the potential risk associated with participation in collision sports. Methods A monocentric retrospective study was conducted at the Rothschild Foundation Hospital (Paris, France), involving 88 professional athletes with an average age of 26 years, predominantly male (80%). All participants underwent comprehensive ophthalmological screening, including fundus examination and ultra-widefield (UWF) retinal imaging of both eyes. Athletes were categorized based on their sport type: collision sports (62%, primarily rugby) and non-collision sports. The efficacy of UWF imaging was compared to dilated fundus examination for detecting peripheral retinal lesions. Results Peripheral retinal lesions were significantly more prevalent in collision sport athletes: 40.5% [30.0–51.0%] for rugby, 40.0% [9.6–70.4%] for boxing and 12.5% [0.0–28.7%] for judo, compared to non-collision sport athletes (6.1% [3.0–11.8%]). The diagnostic sensitivity of UWF imaging was relatively low at 45.2% [34.1–56.2%], though it showed high specificity at 93.6% [88.2–99.0%] when compared to dilated fundus examination. Conclusion The study highlights a higher prevalence of peripheral retinal lesions in elite athletes engaged in collision sports. These findings emphasize the need for regular ophthalmological evaluations in this population to mitigate potential risks associated with asymptomatic retinal damage.